Regulatory variation within 3'UTR of STAT5A correlates with sudden cardiac death in Chinese populations - Huan Yu; Yadong Guo; Zhenzhen Yang; Qing Zhang; Jiabin Xu; Qi Yang; Yiling Qu; Rui Tan; Lijuan Li; Yan He; Chengtao Li; Suhua Zhang; et al. (Oxford University Press, 2021)
Definitive diagnosis to sudden cardiac death (SCD) is often challenging since the postmortem examination on SCD victims could hardly demonstrate an adequate cause of death. It is therefore important to uncover the inherited risk component to SCD. Signal transducer and activators of transcription 5 A (STAT5A) is a member of the STAT family and a transcription factor that is activated by many cell ligands and associated with various cardiovascular processes. In this study, we performed a systematic variant screening on the STAT5A to filter potential functional genetic variations. Based on the screening results, an insertion/deletion polymorphism (rs3833144) in 3'UTR of STAT5A was selected as the candidate variant. A total of 159 SCD cases and 668 SCD matched healthy controls was enrolled to perform a case-control study and evaluate the association between rs3833144 and SCD susceptibility in Chinese populations. Logistic regression analysis showed that the deletion allele of rs3833144 had significantly increased the SCD risk (odds ratio (OR) = 1.54; 95% confidence interval (CI) = 1.18-2.01; P = 0.000955). Further genotype-expression eQTL analysis showed that samples with deletion allele appeared to lower expression of STAT5A, and in silico prediction suggested the local 3 D structure changes of STAT5A mRNA caused by the variant. On the other hand, the bioinformatic analysis presented that promoters of RARA and PTGES3L-AARSD1 could interact with rs3833144, and eQTL analysis showed the higher expression of both genes in samples with deletion allele. Dual-luciferase activity assays also suggested the significant regulatory role of rs3833144 in gene transcription. Our current data thus suggested a possible involvement of rs3833144 to SCD predisposition in Chinese populations and rs3833144 with potential function roles may become a candidate marker for SCD diagnosis and prevention.